An approach to determine suitable mining ground and quantifying mineability risk for diamond mining vessels in the Atlantic 1 mining licence, offshore of Namibia - Kubirske, Tanja (Rhodes University, 2026)
Diamonds are recovered offshore of the southern coast of Namibia in the Atlantic 1 mining licence (Mining Licence 47). In the mining licence the diamondiferous gravel is mostly found in an unconsolidated form, with occasional semi consolidated gravel. Areas of competent outcrops also exist but are considered unmineable with current technology. This is due to the design of the current mining tools, that were created to remove the unconsolidated sediments from the seafloor. Two main technologies are currently deployed within the company, namely the crawler mining tools and the drill bit mining tools (big bits and small bits). Both technologies have their strengths and weaknesses when it comes to the mining terrain, whereby the drill bits can handle rougher terrains while the crawlers are better suited in smooth terrains. Multibeam bathymetric data is collected on all prospective areas within the mining licence, before any sampling or mining takes place. This data provides valuable input in aiding the visualisation of the seabed, as well as the nature of the terrain. Bathymetric data, together with sampling data, is used to determine the suitability of each mining tool to mine an area. For this study, new ways of determining vessel applicability to certain areas have been investigated, as well as determining the risk of mining those areas. A three pronged approach was applied. The first part utilised the benthic terrain mapping method to assess if the outputs can be used to categorise geological features and thereby develop zones of different vessel ground suitability. The second part was to create sedimentary facies maps over the area, to determine if this adequately classifies the different geological features in the study area. The third part was to use the existing sampling information to quantify the mineability and associated risk of an area for each vessel group (small bits, big bits and crawlers).
Keywords: Uncatalogued